Effect of low partial hydrogen in a mixture with methane on the mechanical properties of X70 pipeline steel. (13th January 2020) - Nguyen, Thanh Tuan; Park, Jaeyeong; Kim, Woo Sik; Nahm, Seung Hoon; Beak, Un Bong
Abstract: In this study, the effect of a low partial hydrogen in a mixture with natural gas on the tensile, notched tensile properties, and fracture toughness of pipeline steel X70 is investigated. An artificial HE aging is simulated by exposing the tested sample to the mixture gas condition for 720 h. In addition, a series of tests is conducted in ambient air and 10 MPa of 100% He and H2 . Overall, 10 MPa of 100% H2 significantly degrades the mechanical properties of an X70 pipeline steel. However, it is observed that the 10 MPa gas mixture with 1% H2 does not affect the mechanical properties when tested with a smooth tensile specimen. In the notched tensile test, a significant reduction in loss in the area is observed when tested with a notched specimen with a notch radius of 0.083 mm. It is also confirmed that a 10-MPa gas mixture with 1% H2 causes a remarkable reduction in the toughness. The influence of the exposure time to 1% hydrogen in a mixture with natural gas was found to be minor. Graphical abstract: Image 1 Highlights: Tensile, notched tensile, and toughness of X70 steel under a low partial hydrogen in natural gas mixture were investigated. Significant loss of the reduction in the area was only observed when tested with a sharp notched specimen. Fracture toughness of X70 pipeline steel was reduced markedly under a gas mixture with 1% H2 . Long-term exposure to hydrogen/natural mixture had no remarkable effect.